Modernization as a factor in increasing the efficiency of state financial control (Journal of actual problems of jurisprudence, 2018)
Organization and functioning of a clear system of state financial control - mandatory and indispensable element of fiscal policy, and therefore to improve the system of financial control should be carried out not independently, but as a link in the whole complex of measures of the national system of regulation of social relations that reveals omissions principles of legality, efficiency and economy of material consumption resources at an earlier stage in order to be able to take appropriate corrective measures, and subsequently to develop and implement measures aimed at preventing the occurrence of such violations. In light of the reform of the executive power is actualized the problem of modernization of the entire system of state financial control.Key words: control, financial control, government, modernization.